Tectonic Evolution of the Altun and Karakorum Mountains - Jiandong, Zheng (Journal of Nepal Geological Society, 1995)
The Altun and Karakorum Mountains lie on the northwestern edge of Tibet. Because of their remote setting these regions were essentially unknown. Recently the author took part in the field investigations in the Altun Mountains and surrounding areas, such as Tarim and Qaidam Basins, and West Kunlun Mountains. Based on the practical data, this paper briefly deals with geological background of the Altun and Karakorum Mountains and discusses an intracontinental subduction or A-type subduction along southwestern margin of the Tarim Basin.